Managerial Ownership as a Controller of Earnings Quality in Jakarta Islamic Index 70 - Paryati, Retno (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2024)
Profit is declared quality if it is consistent, does not fluctuate, and can predict the following year's profit. Companies with low levels of profit fluctuation pose managerial challenges because various factors influence the rise and fall of profitability. This research aims to determine the effect of earning Management on Earning Quality with Managerial Ownership as a Moderating Variable in Jakarta Islamic Index 70 (JII70) Companies for the 2019-2021 Period. This research uses the Moderated Regression Analysis (MRA) method in the form of panel data with purposive sampling techniques. The sample used was 18 companies registered in JII70 for the 2019-2021 period. The analytical methods used include descriptive statistical tests, stationarity tests, panel data regression tests, coefficient of determination (R2), F tests, T tests, classical assumption tests, and MRA tests. The research results show that the Earnings Management variable has a negative and significant effect on Earnings Quality. and the Managerial Ownership variable can moderate the influence of Earnings Management on Earnings Quality.